Rancang Bangun Game Edukasi Mengenal Resep Kue Khas Masyarakat Lampung Berbasis Android - Dodi Afriansyah (Jurnal Teknologi dan Informatika (JEDA), 2021)
AbstractTypical cakes or traditional cakes are snacks that have special characteristics and come from a certain area whose recipes are passed down from generation to generation in people's lives, such as getuk, dodol, wajik and many more, each of which has a special taste and characteristic and originates from different places. different. Currently, typical cakes or traditional cakes are less desirable and are also increasingly being forgotten. This is due to the limitations of parents who are willing to spend their time teaching traditional cake making recipes, in addition to the long process and recipes for which only some people know. Based on this, the combination of educational games and recipe books for the Lampung people is the main focus of this research. The introduction of typical cake recipes with a fun concept that makes it easy for users to learn which is packaged in the form of an Android-based educational game. Educational game application contains 10 cake recipes, jigsaw puzzle games and answers from games. The educational game proposed by the researcher is in the form of a technology introduction model that is packaged in the form of a game that not only focuses on stage by stage but also on the introduction of recipes and cake material in the introduced game.